Unveiling the drivers of patient satisfaction in the United States hospitals: Assessing quality indicators across regions. - Man Hung; Sharon Vu; Eric S Hon; Logan Reese; Jacob Gardner; Martin S Lipsky (PLoS ONE)
Introduction Patient satisfaction in the UnitedStates (U.S.) healthcare varies regionally due to cultural, socioeconomic, and infrastructure differences. The Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey measures patient satisfaction across several aspects, including staff responsiveness and hospital environment. This survey influences Medicare reimbursements and helps ensure equitable, high-quality care nationwide. Analyzing these results is crucial for enhancing patient-centered care and understanding regional disparities. Methods This study analyzed HCAHPS data from 3,286 U.S. hospitals from July 1, 2021, to June 30, 2022. Hospitals were stratified by region. The categories analyzed included cleanliness, communication, staff responsiveness, medication information, discharge processes, care transition, overall rating, quietness, and hospital recommendations. Kruskal Wallis tests and heat maps were used to compare and visualize regional differences. Results The analysis revealed significant regional differences in hospital performance across the U.S. (p < 0.05). The Midwest consistently scored the highest in hospital performance metrics, while the "Other" region reported the lowest scores with discharge information, 12.91 percentage points (pp) lower than the Midwest. The communication about medicines indicator scored the lowest across all regions, with the Midwest the best at 76.88, 1.67 pp higher than the West and 9.94 pp higher than the "Other" region. State-level heatmaps highlighted disparities, with New York and South Carolina performing poorly, while South Dakota earned 5-star ratings for overall hospital ratings. Conclusions U.S. healthcare service ratings demonstrate regional disparities, with the Midwest scoring highest overall. The study identified specific areas needing improvement in lower-performing states, contrasting with strong performances in others. These findings can guide policymakers in enhancing national healthcare quality by addressing regional challenges and learning from high-performing states. Understanding these disparities is crucial for improving patient-centered care, reducing quality gaps, and ensuring equitable access to high-quality healthcare across the U.S.